Direitos humanos e dilemas da democracia no Brasil: um estudo sociológico do trabalho policial (1985-2009) - Lima, Cristiane do Socorro Loureiro (2010)
According to the Public National Security Plan, the security is "[ ] a right by democratic excellence legitimately desired by all sectors of society, which is the fundamental right of citizenship, obligation of the constitutional state and responsibility of each one of us." The 1988 Constitution recognized the rights of life, liberty and personal integrity, considered torture and racial discrimination as crimes. The prime directive of the National Security and Citizenship (Law No. 11,707 of June 19, 2008 - PRONASCI-Brazil) expresses the commitment of the Brazilian state with the promotion of human rights. But despite this formal recognition, official violence continues to be used as a means of maintaining social order, consolidating a police action violating human rights (Amnesty International report "They go in shooting" - AI Index: AMR 19/025/2005) . This thesis analyzes the police work combined with the extension of citizenship rights, the spaces of freedom and democracy as a measure for the degree of affirmation or denial of the Human Rights in Brazil, and proposes the construction of a human friendly Police Force (Post - Colonial, Post-Abyss, Intercultural and Democratic)